(untitled) (Economic and Political Thought, 2015)
The author argues that the economic condition of our societies has to be viewed over a very long historical scale. The assumption made by Francis Fukuyama that history had somehow come to an end with the collapse of the former Soviet empire has proved to be an illusion. Fukuyama was there implying that the system of neoliberal economics had proved itself to be the key to human happiness and welfare, and that once in place, nothing could equal it. But after a quarter of a century, the doctrines of free market economics are coming under increasing criticism. In many countries in which the principles have been applied, not only the traditional working classes are feeling the pain as unemployment has risen, and incomes have remained static even for those in work. The middle classes are also complaining about reduced expectations of prosperity, in the sense of static or even falling incomes. It is obvious that younger generations are entering the workplace with heavy debts from the cost of university education, and rises in the property market are putting the ambition of home ownership beyond their reach. But all this has to be considered in the hard light of history. Why should capitalism, which has hardly existed for five centuries, be considered the default system for all future time, when the trail of collapsed civilisations goes back to the dawn of human existence on earth? But the wrangles of economists and politicians may be set at naught by forces that may be entirely outside their control. Climate change may cause enormous damage even in the present century. Linked with that is the question of mass migration, the consequences of which are now plain to see. And scientists may experiment with artificial intelligence at their peril. Once machines acquire the ability to modify themselves, all may be over for capitalism – and the human race.